2008
DOI: 10.1091/mbc.e07-05-0430
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Activates Pancreatic Calcineurin-NFAT Signaling In Vitro and In Vivo

Abstract: Elevated endogenous cholecystokinin (CCK) release induced by protease inhibitors leads to pancreatic growth. This response has been shown to be mediated by the phosphatase calcineurin, but its downstream effectors are unknown. Here we examined activation of calcineurin-regulated nuclear factor of activated T-cells (NFATs) in isolated acinar cells, as well as in an in vivo model of pancreatic growth. Western blotting of endogenous NFATs and confocal imaging of NFATc1-GFP in pancreatic acini showed that CCK dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 72 publications
1
42
0
1
Order By: Relevance
“…NFAT-Luciferase Activity Assay-Acinar cells were infected with Ad-NFAT-luciferase following a previously described procedure (26). The construct includes a luciferase gene placed downstream of an IL-4 promoter that contains nine tandem NFAT binding sites.…”
Section: Methodsmentioning
confidence: 99%
“…NFAT-Luciferase Activity Assay-Acinar cells were infected with Ad-NFAT-luciferase following a previously described procedure (26). The construct includes a luciferase gene placed downstream of an IL-4 promoter that contains nine tandem NFAT binding sites.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated genes upregulated at any point in the course of our 1-8 h profile of pancreatic growth (Ն3-fold induction vs. fasting and q Յ 0.04 -0.06), yielding a set of 314 genes. In addition, we also used a previously defined set of 51 probes, representing 38 unique CN-dependent genes (10). Analyzing the two groups in conjunction via MCM, we showed associations with growth factor activity, cytoskeletal organization and apoptosis, NF-B and Jak-STAT signaling, as well as two literature-derived concepts related to differentiation (Fig.…”
Section: Defining the Genetic Program Of Cck-mediated Pancreatic Growthmentioning
confidence: 97%
“…This concept is not without precedent in the exocrine pancreas. We have shown that NFATs, known to be involved in T-cell differentiation and cytokine production (25), are activated in the course of CCK-mediated pancreatic growth (10). Furthermore, a key transcriptional effector of microbial and cytokine-induced signaling, NF-B, has now been shown to be activated in pancreatitis and may be an important determinant of disease severity (34).…”
Section: -Treated Micementioning
confidence: 99%
See 1 more Smart Citation
“…68 important social institution in the lives of its members," the Catholics must have felt that all other alternatives were exhausted or that the priests exaggerated the evils of Socialism. 73 For Milwaukee Catholics to break with tradition and the focal point of their lives was unprecedented and makes their political shift all the more dramatic. The 1910 election, and the Catholics' support of the SocialDemocratic Party, demonstrates the extent to which "the gap between cleric and lay had only widened."…”
mentioning
confidence: 99%